CHARACTERISTICS AND SEDIMENT DISTRIBUTION OF COASTAL MAMUJU DISTRICT - Rahmat Januar Noor (Hasanuddin University, 2019)
This study aims to determine the basic sedimentary profile and distribution of TSS in the coastal areas of Mamuju Regency. The research method used a case study with data collection using field survey tec hniques and sample testing in the laboratory. The data was then analyzed descriptively using tabulation techniques and making sediment distribution maps. The results showed that sediment at the study site was dominated by coarse sand with a total organic matter content (BOT) of 1.59 mg / L which was still below the quality standard (<10 mg / L) but the TSS concentration at water bodies of 26.80 mg / L have passed the quality standard for coral reef and seagrass ecosystems (20 mg / L)